Designing a Virtual Exhibition of Children's Drawings for Parents to Learn About Their Child's Growth and Development - Amalia Ghaisani; Antonius Edi Widiargo; Lukas Sugiyanto (SEAN Institute, 2026)
This study aims to determine the physical and psychological development of children interpreted through children's drawings. The research method uses research and development with a descriptive approach. The design technique uses 3D Vista while data collection is done by observation and interviews. The design results educate parents about child development through visual representation in a virtual exhibition that can be accessed online and form a dynamic platform in child education and parental involvement.